Pharmacological Developments Obtained from Marine Natural Products and Current Pipeline Perspectives (2011)
ABSTRACT: Marine organisms represent a new extensive source for bioactive molecules. They have the potential to provide new therapeutic alternatives to treat human diseases. In this paper, we describe and discuss a variety of isolated and semisynthetic molecules obtained from marine phase II, phase III and at the commercialization stage of new drug development. A description of the mechanism of action, dosage used and side effects are also reported. The positive results obtained from these studies have triggered the development of new studies to evaluate the prospects for utilization of marine organisms.